Gametogenesis and spawning of Spirobranchus tetraceros (Polychaeta, Serpulidae) in Abu Kir Bay, Egypt - SELIM, S. A.; ABDEL NABY, F.; GAB-ALLA, A.A. F.A.; GHOBASHY, A. (Mediterranean Marine Science, 2005)
The serpulid polychaete Spirobranchus tetraceros of Red Sea / Indo-pacific origin, recently has succeeded to establish a foothold in Alexandria Mediterranean waters. Worms were monthly scraped from submerged iron substrates at Abu Kir Bay during the period December 2000 – November 2001. Both light and TEM were used to study gametogenesis and time of spawning of S. tetraceros.Gametogenesis was asynchronous and oogenesis could be divided into two previtellogenic, two vitellogenic and a spawning stage. Oocyte development took about 8 months, from October to June. Spawning occurred from late May - early June until October. Thus S. tetraceros is a long period spawner. The maximum diameter of ripe oocyte is 78 mm. The spermatogenic phase could be divided into three stages: spermatogonia, spermatocytes and spermatids (including spermatozoa). The duration of sperm development took about 8 months. Spermatocytes persist from October to March. By March the sperms grew rapidly until they became spermatozoa in May. The sperm could be considered ect-aquasperm with regard to its fertilization biology.